In situ rutile U-Pb dating based on zircon calibration using LA-ICP-MS, geological applications in the Dabie orogen, China. (1st May 2020) - Hou, Zhenhui; Xiao, Yilin; Shen, Ji; Yu, Chenglong
Graphical abstract: Highlights: Zircon is good calibration standard for rutile dating with spot size of 44–90 µm. Elemental fractionation between rutile and zircon was intensively investigated. Two ages of rutile from the Dabie UHP rocks suggest different exhumation history. Abstract: Rutile U-Pb dating by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) has received increasing attention in geological applications. Previous natural rutile reference materials are insufficient to meet the growing demand of working standards for laser U/Pb dating. In present study, we have developed a new calibration strategy for LA-ICP-MS rutile dating using the most popular zircon as reference material. The matrix-dependent elemental fractionation of rutile and zircon could effectively decrease to a better level by optimized analytical parameters and with large ablation spot size (44–90 µm). The acceptable Pb/U correction coefficient between rutile and zircon could be obtained while the diameter/depth ratio of the crater is above 1 after assessing elemental fractionation of different ablation size. Five rutile were analyzed by zircon calibration, and their ages show strong agreement with those obtained by secondary ion mass spectrometry (SIMS) or thermal ionization mass spectrometry (TIMS) analysis, with both precision and accuracy within ±2%. Two rutiles of eclogitic rocks from the Dabie orogen yield the ages of 207.0 ± 2.1 Ma and 205.6 ± 2.4 Ma, respectively. Both ages are conceivably younger than that previously reported rutile ages (218 Ma) for eclogites. The quite different U-Pb ages of rutile from different localities most likely indicate the different exhumation history of the subducted continental crust. LA-ICP-MS rutile U-Pb dating using zircon as an external calibration reference material would assuage rutile reference material insufficient supply and improve its widespread application.